Gamification for Science Learning Media Challenges of Teacher and Expectations of Students - Lutfi, Achmad; Hidayah, Rusly (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The purpose of this research is to determine the response of teachers and students towards the use of computer-based games as a medium for learning Sciences. Data were obtained from students of two ninth-grade classes of Junior high school in Surabaya, East Java, Indonesia, through observation, questionnaire, and interviews. Science learning on atomic subjects was carried out by each science teacher, while students used computerized games and worksheets. The results showed that 87.50% to 100% of students supported the use of computer-based games as a science learning media to achieve the specified target. Meanwhile, teachers believe that the use of this technique is very good because it enables students to play and learn. Therefore it has the ability to prevent them from participating in uneducational games.